Policies and institutions for development territorial economic (Revista LIDER, 2021)
An international comparative research on 10 Latin American countries conducted by ILPES, has shown an increasing interest of national authorities on regional development. A family of territorial policies has been created, including local development, land planning, and decentralization. Nevertheless, central authorities have not realized yet the coordination challenges there are facing: between sectors and levels (national, intermediate and local). At the same time, localities and territories need a new kind of decentralized diplomacy to take advantage of these new set of opportunities. In practical an theoretical terms, it is extremely important to realize that there is a new space of confluence between local (down-top) and regional development policies (top-down) named Territorial Economic Deveolpment Policy